2020
DOI: 10.3390/plants9121710
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Ripening-Specific Accumulation of Polyamines Spermidine and Spermine in Tomato Fruit Upregulates Clustered C/D Box snoRNA Gene Transcripts in Concert with Ribosomal RNA Biogenesis in the Red Ripe Fruit

Abstract: Ripening of tomato fruit leads, in general, to a sequential decrease in the endogenous levels of polyamines spermidine (SPD) and spermine (SPM), while the trend for the diamine putrescine (PUT) levels is generally an initial decrease, followed by a substantial increase, and thereafter reaching high levels at the red ripe fruit stage. However, genetic engineering fruit-specific expression of heterologous yeast S-adenosylmethionine (SAM) decarboxylase in tomato has been found to result in a high accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…We also identified several genes in the co-expression networks that were related to abiotic stress responses and/or expressed in fruits, such as SPS1 (Solyc07g007790), SlPDI7-2 (Solyc11g019920), SlMC8 (Solyc10g081300), SlWRKY1 (Solyc07g047960), SlWRKY3 (Solyc08g081610), Solyc07g064820 (Mitogen-activated protein kinase kinase 2-like), Solyc07g040960 (Salt responsive protein 2), and SlGPAT6 (Solyc09g014350) in the co-expression network of SlHVA22g [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ]; SlRabGAP9a (Solyc07g049580), SlRabGAP21a (Solyc12g009610), SlGT-33 (Solyc12g043090), SlFdAT1 (Solyc12g088170), Solyc11g045120 (Translation initiation factor SUI1), and Solyc11g044910 (β-D-xylosidase) in that of SlHVA22k [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ]; and Solyc10g078600 (phosphate transporter 1-1), C2H2 zinc finger ( C2H2-ZF ) (Solyc11g017140), Solyc11g045120 (Translation initiation factor SUI1), Solyc11g044910 (β-D-xylosidase), SlRabGAP9b (Solyc12g005930), SlRabGAP21a (Solyc12g009610), and SlFdAT1 (Solyc12g088170) in that of SlHVA22l [ 57 , 58 , 59 , 62 , 64 , 65 ] ( Figure 6 and Table S12 ). These findings suggest that these three genes, whose transcript levels were high in fruit and induced by abiotic stresses, likely function together with the co-expressed genes in the fruit development and abiotic stress response of tomato.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified several genes in the co-expression networks that were related to abiotic stress responses and/or expressed in fruits, such as SPS1 (Solyc07g007790), SlPDI7-2 (Solyc11g019920), SlMC8 (Solyc10g081300), SlWRKY1 (Solyc07g047960), SlWRKY3 (Solyc08g081610), Solyc07g064820 (Mitogen-activated protein kinase kinase 2-like), Solyc07g040960 (Salt responsive protein 2), and SlGPAT6 (Solyc09g014350) in the co-expression network of SlHVA22g [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ]; SlRabGAP9a (Solyc07g049580), SlRabGAP21a (Solyc12g009610), SlGT-33 (Solyc12g043090), SlFdAT1 (Solyc12g088170), Solyc11g045120 (Translation initiation factor SUI1), and Solyc11g044910 (β-D-xylosidase) in that of SlHVA22k [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ]; and Solyc10g078600 (phosphate transporter 1-1), C2H2 zinc finger ( C2H2-ZF ) (Solyc11g017140), Solyc11g045120 (Translation initiation factor SUI1), Solyc11g044910 (β-D-xylosidase), SlRabGAP9b (Solyc12g005930), SlRabGAP21a (Solyc12g009610), and SlFdAT1 (Solyc12g088170) in that of SlHVA22l [ 57 , 58 , 59 , 62 , 64 , 65 ] ( Figure 6 and Table S12 ). These findings suggest that these three genes, whose transcript levels were high in fruit and induced by abiotic stresses, likely function together with the co-expressed genes in the fruit development and abiotic stress response of tomato.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines are organic compounds having more than two amino groups, and with a role in several physiological functions, such as DNA synthesis, cellular proliferation, differentiation, and response to abiotic and biotic stresses [16][17][18][19]. Many findings have demonstrated the important properties of these polycations.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the PA Put in extending tomato fruit shelf life has recently come into focus, together with Spd and Spm ( Gupta et al, 2019 ; Osorio et al, 2020 ). Notably, Spd/Spm may regulate small nucleolar RNAs (snoRNAs) and ribosomal RNA (rRNA) expression directly or indirectly, which in turn will affect protein biosynthesis, metabolism, and other cellular activities in a positive manner ( Shukla et al, 2020 ).…”
Section: Roles Of Pas In the Ripening Senescence And Quality Of Flementioning
confidence: 99%
“…In non-climacteric fruits, such as strawberry ( Fragaria ananassa ), ripening is largely controlled by ABA ( Li et al, 2011 ; Shen and Rose, 2014 ). In addition to ABA and ethylene, a series of studies also suggested a critical role for PAs in fruit ripening ( Dibble et al, 1988 ; Kushad et al, 1988 ; Rodriguez et al, 1999 ; Lester, 2000 ; Bregoli et al, 2002 ; de Dios et al, 2006 ; Mattoo et al, 2006 , 2007 , 2010 ; Handa and Mattoo, 2010 ; Parra-Lobato and Gomez-Jimenez, 2011 ; Koushesh saba et al, 2012 ; Gupta et al, 2013 ; Fortes et al, 2015 ; Jiang et al, 2015 ; Simpson et al, 2017 ; Guo et al, 2018 ; Liu et al, 2018 ; Shukla et al, 2020 ). In the past several years, many reviews have explored the roles of ABA and ethylene in the ripening of fleshy fruits, while a handful of reviews have reported on the roles of PAs in response to development and stress in plants ( Kusano et al, 2018 ; Chen et al, 2019 ; Fortes et al, 2019 ; Wang et al, 2019 ; Killiny and Nehela, 2020 ).…”
Section: Introductionmentioning
confidence: 99%